Complete Nucleotide Sequence, Genome Organization, and Comparative Genomic Analyses of Citrus Yellow-Vein Associated Virus (CYVaV) - Kwon, Sun-Jung; Bodaghi, Sohrab; Dang, Tyler; Gadhave, Kiran R.; Ho, Thien; Osman, Fatima; Al Rwahnih, Maher; Tzanetakis, Ioannis E.; Simon, Anne E.; Vidalakis, Georgios (Frontiers in Microbiology, 2021)
Citrus yellow-vein disease (CYVD) was first reported in California in 1957. We now report that CYVD is associated with a virus-like agent, provisionally named citrus yellow vein associated virus (CYVaV). The CYVaV RNA genome has 2,692 nucleotides and codes for two discernable open reading frames (ORFs). ORF1 encodes a protein of 190 amino acid (aa) whereas ORF2 is presumably generated by a –1 ribosomal frameshifting event just upstream of the ORF1 termination signal. The frameshift product (717 aa) encodes the RNA-dependent RNA polymerase. Phylogenetic analyses suggest that CYVaV is closely related to unclassified virus-like RNAs in the family Tombusviridae. Bio-indexing and RNA-seq experiments indicate that CYVaV can induce yellow vein symptoms independently of known citrus viruses or viroids.